Experimental study on elastic deformation molding process for generating aspheric surface glass. Issue 5 (February 2016) - Nguyen, Ducnam; Yuan, Julong; Wu, Zhe
Abstract The elastic deformation machining method has been demonstrated to be a novel optical manufacturing approach which can greatly reduce and simplify the production of large aspheric lens. Upon completion of the machining process, the workpiece under process will be shaped into a desired surface form of mold. The method allows the lapping and polishing of aspheric optical surfaces using a large lapping or polishing tools. The subject of this study is to determine the surface shape of the finished glass workpiece after the lapping process of the elastic deformation machining process associated with molding. The experimental and finite element analysis (FEA) results were compared with the shape of the molded surface form. The form accuracy between the optical glass and mold is within 1.6 μm (within radius 32 mm). The conclusions show that the method proposed is effective for machining the aspheric optical glass with proper elastic deformation machining parameters.